Political Polarization in Social Media: A Meta-Analysis - Subekti, Dimas; Mutiarin, Dyah (Thammasat Review, 2023)
The problem of political polarization in social media is increasingly dynamic. Therefore, the contribution of this research is more to develop the concept of political polarization in social media, by exploring the research that has been done related to this topic. This study uses the scoping review method. The findings in this study that the development of research on political polarization in social media has become very rapid in the last twelve years in line with technological developments. This is because the virtual world becomes a facility for political polarization to occur. Interestingly, Twitter and ideology are very strong keywords related to this topic. This indicates that Twitter is the most dominant place for political polarization with the cause being ideological differences. Furthermore, keywords that have the opportunity to be investigated further in the future are political discourse, elections, democracy, and political participation in the big theme of political polarization.